CLINICAL EFFICACY OF IBUPROFEN IN THERAPY FOR VIRAL UPPER RESPIRATORY TRACT INFECTIONS IN INFANTS - I.O. Skugarevskaya; Yu.V. Ivanova; O.K. Botvin'ev; Osama Al-Handy (Union of pediatricians of Russia, 2006)
A study of use of ibuprofen in cases of viral upper respiratory tract infections (Vuri) in children of early childhood has proved its' safety and efficacy. This medical agent has not only terminate fever but also diminished some other symptoms of Vuri.Key words: ibuprofen, viral upper respiratory tract infections, children.